Allocation of foreign direct investment across brazilian states - Bortoluzzo,Maurício Mesquita (2013)
Foreign direct investment (FDI) has become increasingly important for the Brazilian economy: the ratio of FDI inflow to the country's gross domestic product (GDP) increased from a 0.6% average in the 1980's to 2.5% from 2001 to 2010, according to data from UNCTAD. However, there is great inequality in the distribution of this investment among Brazilian federation units. This study aims at investigating the determining factors for the location of foreign direct investment across Brazilian states, based on an econometric study with panel data for the years 1995, 2000 and 2005. The results showed that foreign investment responded positively to consumer market size, quality of labor and transport infrastructure, but negatively to cost of labor and tax burden.